Numerical Solution of a Space-Time Fractional by Semi-Linear Diffusion Equation - Rekha Rani, Mahender Singh Poonia (Mathematical Statistician and Engineering Applications, 2023)
The objective of the work is to address the underlying limit esteem issue for the semi-direct space-time fragmentary dissemination condition utilizing an implied technique. The fundamental thought behind the methodology is to change over the issue into a logarithmic framework, which makes the calculations simpler. The consistency and security of the methodology are analyzed utilizing the strength framework investigation. Mathematical responses to models of semi straight fragmentary dissemination conditions are given. The acquired information is contrasted with accurate reactions. We inspect the blunder examination of the implied limited contrast plan, assembly, and solidness utilizing reasonable MATLAB models.